2005
DOI: 10.1590/s0100-40422005000300008
|View full text |Cite
|
Sign up to set email alerts
|

Emprego de compostos organometálicos mononucleares de paládio(II) na ativação de macrófagos peritoneais de camundongos

Abstract: Recebido em 3/3/04; aceito em 26/10/04; publicado na web em 17/2/05 ACTIVATION OF MICE PERITONEAL MACROPHAGES BY PALLADIUM(II) ORGANOMETALLIC MONONUCLEAR COMPOUNDS. The immune responses are mediated by a variety of cells that, when activated, produce a number of molecules. Macrophages are the first cells to take part in the immune response releasing many compounds in the extracellular environment such as H 2 O 2 . Taking into account this aspect we evaluated the activation of an immunological system, in vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Recent research has demonstrated that organopalladated compounds containing diphenylphosphine ligands can activate macrophages in vitro (De Almeida et al, 2005) via immunological activation. This effect was demonstrated by assessing the amount of H 2 O 2 released in cultures of peritoneal macrophages from Swiss mice in the presence of organopalladated compounds of the type [Pd(dmba)(X)(dppp)] (dmba = N,N-dimethylbenzylamine; dppp = 1,3-bis(diphenylphosphine) propane; X = Cl, N 3 , NCO, NCS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has demonstrated that organopalladated compounds containing diphenylphosphine ligands can activate macrophages in vitro (De Almeida et al, 2005) via immunological activation. This effect was demonstrated by assessing the amount of H 2 O 2 released in cultures of peritoneal macrophages from Swiss mice in the presence of organopalladated compounds of the type [Pd(dmba)(X)(dppp)] (dmba = N,N-dimethylbenzylamine; dppp = 1,3-bis(diphenylphosphine) propane; X = Cl, N 3 , NCO, NCS).…”
Section: Resultsmentioning
confidence: 99%
“…The organometallic complexes [Pd(dmba)(Cl) tu] and [Pd(dmba)(N 3 )tu] were synthesized according to the literature (Lucca Neto et al, 1998;De Almeida et al, 2005), at the Laboratory of Organometallic and Coordination Chemistry, Department of General and Inorganic Chemistry, UNESP, Araraquara, Brazil. Cisplatin (FH Fauld-ing & Co. Ltd., Adelaide, Australia) was used as standard drug.…”
Section: Organometallic Complexesmentioning
confidence: 99%
“…Our research group has demonstrated that organopalladated compounds containing diphenylphosphine ligands have activated macrophages in vitro 32 by the immunological activation, in vitro, determining the H 2 O 2 released in cultures of peritoneal macrophage cells from Swiss mice in the presence of organopalladated compounds of the type [Pd(dmba)(X)(dppp)], dmba = N,Ndimethylbenzylamine, dppp = 1,3-bis(diphenylphosphine)propane, X = Cl, N 3 , NCO, NCS. An excellent activation of macrophages by the [Pd(dmba)(X)(dppp)] compounds was observed and the influence of the X ligand on the immune response could be verified.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Our previous results have indicated that the release of H 2 O 2 levels in cultures of activated mice peritoneal macrophages was increased in the presence of compounds of the type [PdX(dmba)(dppp)] (X = Cl, N 3 , NCO, NCS; dmba = N,N-dimethylbenzylamine; dppp = 1,3-bis(diphenylphosphine)propane). 14 Metal-based compounds of 1,2,4-triazole have received attention due to their potential uses as antimicrobial and antitumoral drugs.…”
Section: Introductionmentioning
confidence: 99%
“…As ligands, 1,2,4-triazoles are extremely versatile and display the ability to act as monodentate, exobidentate N(1),N (2) and exobidentate N (2),N(4) when neutral or monodentate, exobidentate N (1),N (2), exobidentate N (1), N(4) and N (1),N (2),N(4)-tridentate when deprotonated. 17 In pursuing our interest on chemical and biological aspects of palladium(II) complexes, 14,18,19 we describe in this work the synthesis, spectroscopic characterization and thermal investigation of the two new 1,2,4-triazolylbridged polynuclear complexes [{PdCl 2 (µ-Htrz)} n ] (1) and [{PdBr 2 (µ-Htrz)} n ] (2). We also investigated the immunomodulatory effects of the compounds 1,2,4-triazole (Htrz), 1, 2, and cisplatin by the release of NO and H 2 O 2 in the culture supernatants of treated murine peritoneal cells.…”
Section: Introductionmentioning
confidence: 99%